A Cross-Sectional Study on Quality of Life of Patients with Coronary Artery Disease Attending Out Patient Cardiology Department of a Tertiary Care Hospital, Kolkata - Satyabrata Maity; Debashis Dutta; Bobby Paul; Noor Islam Bag; Chirasree Sarkar (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Developing countries like India prevalence of coronary artery disease (CAD) is increasing day to day from 1.6 percent to 7.6 percent in rural areas and 1.0 percent to 13.6 percent in urban areas in last few decades and it is going to be a double burden near 2035. Indians are known to have the highest coronary artery disease (CAD) rates.Objective: To find out the socio-demographic characteristics and clinical profile of the patients suffering from coronary artery disease (CAD) attending a tertiary care hospital. This study also assessed the health-related quality of life (HRQOL) of patients.Method: A hospital based cross sectional study was done in Patients more than 18 years of age with coronary artery disease attending Cardiology OPD SSKM Hospital in Kolkata. The study was done from the year August 2020 to September 2022. The study was done on 220 patients by using a structured pretested Mac New HRQOL questionnaire. Results: The median age of coronary artery disease patients was 56 (50-62) years. Around one-third portion (34.1%) of the study participants achieved a primary level of education. The Median (IQR) of per capita income (Rs/month) of the study participants was 2000 (1250-3938). Nearly three fourth (71.4%) participants had various types of co-morbidities. Clinically, 88.2% had normal heart rates, 51.4% had normal blood pressure and 43.6% had low ejection fraction. MacNew HRQOL score among participants were 4.7,4.8,4.4 in social, emotional and physical domain, respectively. Conclusion: Male gender, lower socio-economic conditions, low level of education, inadequate dietary diversity patterns and substance user outnumbered their counterpart. The HRQOL was found satisfactory but lacking in physical domain.